Can early exposure to probiotics in children prevent dental caries? A current perspective - Garima Jindal; Ramesh Kumar Pandey; Rajeev Kumar Singh; Neelisha Pandey (Journal of Oral Biology and Craniofacial Research)
Background: Probiotics are supplements or foods that contain viable microorganisms which cause alterations of the microflora of the host. Probiotics have already been established in the treatment and prevention of various gastrointestinal system. Recently, role of probiotics has become an important issue for research in dentistry in the era of increased antibiotic resistance. Materials and methods: The basis of the paper is the clinical studies and research done in relation to probiotics on oral health using PUBMED search database. Results and conclusions: Although many clinical studies have demonstrated positive outcome in preventing caries and periodontal diseases, the data is still scarce in recommending probiotics for the oral health. Moreover, since initial colonization of oral cavity of the newborn is very important for developing immunity and prevention of future diseases. Hence, measures should be directed towards its preventive use in infants and children. The formulations produced for oral cavity should also be within reach of common man especially in underdeveloped and developing countries. This review endeavors to compile the research of probiotics on oral cavity and throws a light on its evolving status in developing countries. It also evaluates its use in children for a long-term benefit.